Analisis faktor-faktor yang mempengaruhi independensi penampilan akuntan publik - Retty Novianty; Indra Wijaya Kusuma (Jurnal Akuntansi dan Auditing Indonesia, 2001)
This study aims to identify and to test factors that effect public acountant's  appearance. The auditor's independence has an important role in the view of companies, investors and the auditor themeselves. Investigation on 75 respondents from public accountant firms and user companies in Indonesia, found that financial interest in the client's company and business relationship with their clients were the only significant factors in affecting the independence. the significant result was not found for non audit services offered by auditors, the lenght of continuiting audit services, the size of the audit firm, competition in providing auditing services among auditors, and audit fees.